PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR SISWA KELAS XI SMA NEGERI 1 LENEK - Dian Sekar Lestari (Cocos Bio, 2025)
Abstract : This study aims to determine the effect of the Project Based Learning (PjBL) learning model on the learning outcomes of grade XI students. The design used in this study is a quasi-experimental design with a nonequivalent control group design that uses two groups, namely the control group and the experimental group. The control group uses the conventional model while the experimental group uses the Project Based Learning (PjBL) model at SMA Negeri 1 Lenek. This design employed a pre-test before treatment and a post-test after treatment, so that the comparison results of the treatment would be more accurate. Based on the calculation of the average test scores, the pre-test and post-test scores of the experimental class were higher than those of the control class. The experimental class obtained a pre-test score of 37.42 and a post-test score of 43.33 with an increase of 5.91. In the control class, the pre-test score was 34.50, and the post-test score was 35.50 with an increase of 1. The normality calculation for the experimental class pre-test was 0.128 < 0.154, categorized as normal, and for the control class pre-test was 0.137 < 0.161, categorized as normal. The post-test calculation for the experimental class was 0.141 < 0.154, categorized as normal, and for the control class post-test was 0.119 < 0.161, categorized as normal. The homogeneity calculation of the pre-test for the experimental and control classes was 1.300 < 1.823, categorized as homogeneous data, and for the post-test of the experimental and control classes was 1.409 < 1.823, also categorized as homogeneous data. Furthermore, the hypothesis calculation for the experimental class obtained a T-count = 2.834 > T-table = 1.997, indicating significant data, while the control class obtained a T-count = 0.392 < T-table = 2.001, indicating non-significant data. Keywords : Project-Based Learning (PjBL), Student Learning Outcomes